2007
DOI: 10.1086/519841
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Type 2 Diabetes Mellitus on the Presentation and Treatment Response of Pulmonary Tuberculosis

Abstract: Background. Diabetes mellitus (DM) is a known risk factor for tuberculosis (TB), and with the increasing prevalence of type 2 DM in less developed regions, many patients with TB will have concomitant DM. Presently, little is known about the effect of DM on the clinical presentation and treatment outcome of TB.Methods. In an urban setting in Indonesia, 737 patients with pulmonary TB were screened for DM and were followed up prospectively during TB treatment. Clinical characteristics and outcome were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
297
12
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(346 citation statements)
references
References 19 publications
22
297
12
15
Order By: Relevance
“…It is widely known that there is higher frequency of pulmonary TB in males. DM patients with TB appear to be older than non DM subjects 25 . DM was classified as type-2 (T2DM) in majority of studies in TB-DM 32 .…”
Section: Clinical Presentationmentioning
confidence: 85%
See 3 more Smart Citations
“…It is widely known that there is higher frequency of pulmonary TB in males. DM patients with TB appear to be older than non DM subjects 25 . DM was classified as type-2 (T2DM) in majority of studies in TB-DM 32 .…”
Section: Clinical Presentationmentioning
confidence: 85%
“…A delay in sputum conversion was observed in TB-DM patients 25,27,[34][35][36] . Restrepo et al 36 reported that within 60 days the mycobacterial clearance was delayed by 5 days.…”
Section: Effect Of Dm On Treatment Of Tbmentioning
confidence: 92%
See 2 more Smart Citations
“…10,11 DM constitutes a risk factor for active TB and might influence the disease presentation and response to treatment. 12,13 On the other hand, TB may induce glucose intolerance and aggravate glycemic control in patients with DM. 14,15 The higher susceptibility of TB in diabetics may be related to a longer duration of disease or due to poor control of glycemic status.…”
mentioning
confidence: 99%